2022
DOI: 10.1002/csr.2399
|View full text |Cite
|
Sign up to set email alerts
|

Communicating corporate social responsibility: How fit, specificity, and cognitive fluency drive consumer skepticism and response

Abstract: This research examined consumer responses to a company's communication of its corporate social responsibility (CSR) initiatives. Two prestudies verified the impact of company-cause fit and message specificity on consumer skepticism toward CSR initiatives. These studies also showed that the resulting skepticism mediated the consumer responses. The main study explored how company-cause fit and message specificity jointly influenced consumer skepticism and how this could be mediated by cognitive fluency. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 69 publications
0
0
0
Order By: Relevance
“…As supported by the previous literature [9,20,22,70], the current study showed the positive effect of specific messages compared to abstract messages. While scholars have primarily focused on the role of CSR message specificity in consumer perceptions of company trustworthiness [68,71], our study expands the understanding of message specificity by investigating its effects on CCI, WOM intention, and CSR participation intention, which have not previously been extensively studied.…”
Section: Discussion Of Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…As supported by the previous literature [9,20,22,70], the current study showed the positive effect of specific messages compared to abstract messages. While scholars have primarily focused on the role of CSR message specificity in consumer perceptions of company trustworthiness [68,71], our study expands the understanding of message specificity by investigating its effects on CCI, WOM intention, and CSR participation intention, which have not previously been extensively studied.…”
Section: Discussion Of Resultssupporting
confidence: 90%
“…Increased stakeholder awareness can be achieved through corporate efforts to share detailed information about CSR activities, such as specific commitments, social impact, and motives for CSR engagement [8]. Previous research has demonstrated the effects of message specificity on various outcomes, such as message evaluations [9,[18][19][20], consumer perceptions of companies [17,21], and behavioral intentions [11,22].…”
Section: Literature Review 21 Message Specificity In Csr Communicationmentioning
confidence: 99%
See 3 more Smart Citations